2022
DOI: 10.1177/02654075221108760
|View full text |Cite
|
Sign up to set email alerts
|

The role of relational mobility in relationship quality and well-being

Abstract: This paper examined the associations among: (1) the perceived freedom to initiate and end interpersonal relationships ( relational mobility), (2) relationship quality, and (3) well-being. Across 38 nations, people in nations with higher relational mobility reported greater well-being, which was explained by higher-quality relationships with close others (Study 1A). This effect was replicated at the individual level, after controlling for extraversion and socio-economic status (Study 1B). Finally, first-year co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Although we observed differences in perceived positivity resonance (a desired social outcome) across countries, it will be worthwhile to test for sequential mediation via which relational mobility explains cultural differences in adaptive strategies such as emotion expressiveness, which in turn predict downstream desired social outcomes such as positivity resonance. As prior research has suggested that cultural variations in the quality of relationships with strong social ties contribute to differing levels of well-being (B. Park et al, 2022), it is also essential to investigate potential cultural differences in the extent to which the effects of co-experienced kind-hearted positive emotions cascade toward relational, mental, and physical well-being.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we observed differences in perceived positivity resonance (a desired social outcome) across countries, it will be worthwhile to test for sequential mediation via which relational mobility explains cultural differences in adaptive strategies such as emotion expressiveness, which in turn predict downstream desired social outcomes such as positivity resonance. As prior research has suggested that cultural variations in the quality of relationships with strong social ties contribute to differing levels of well-being (B. Park et al, 2022), it is also essential to investigate potential cultural differences in the extent to which the effects of co-experienced kind-hearted positive emotions cascade toward relational, mental, and physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on relational mobility found that higher relational mobility is associated with greater intimacy with strong social ties (B. Park et al, 2022). We consider positivity resonance, a collective experience indicative of high-quality social interactions and strengthening social bonds, as another desired social outcome of these adaptive strategies.…”
Section: Relational Mobilitymentioning
confidence: 95%
See 2 more Smart Citations